Análise molecular de polimorfismos e expressão gênica do fator β1 de transformação do crescimento (TGF-β1) no câncer de próstata - Faria, Paula Cristina Batista de (2005)
In recent decades, prostate cancer has emerged as one of the most common diseases among older men. In Brazil and the United States is the second most commonly diagnosed after non-melanoma skin cancer. Also, it is the second cause of death in men after lung cancer. Among the cytokines that make up the family of Transforming Growth Factors p (TGF-ps), TGF-pi is most often overexpressed in tumor cells and plays a central role in tumor transformation and progression as well as tumor repression; being the main focus of most studies on the role of growth factors in tumorigenesis. Several studies have shown that somatic mutations in TGF-Î²1 and other components of its signaling pathway are also associated with tumor development. In the present study, TGF-β1 gene expression in peripheral blood samples from patients with prostate adenocarcinoma (CaP) and benign prostatic hyperplasia (BPH) was evaluated by semi-quantitative RT-PCR. clinical presentation of patients, disease staging, and also the presence of the LeulOPro (T and C alleles) and Arg25Pro (alleles G and C) polymorphisms, present in exon 1 of the TGFB1 gene. The technique used for patient genotyping was PCR-ARMS, which proved to be very efficient for this. No statistically significant differences were observed between the genotypes and the patient groups analyzed. However, the presence of the C allele in Codon 10 may be involved in the progression of cancer once installed, since a trend was observed between patients with CaP and patients with this disease. allele in presenting a higher Gleason score. We also found a higher level of TGFB1 gene transcripts in patients with CaP, suggesting that this may be a potential serum biomarker for prostate cancer. However, subsequent studies are needed to better understand the role of this cytokine in the development and progression of this disease.